Detection of Infectious Bursal Disease Virus in Field Outbreaks in Broiler Chickens by Reverse Transcription-Polymerase Chain Reaction - Mittal, D.; Jindal, N.; Gupta, S.L.; Kataria, R.S.; Tiwari, A.K. (International Journal of Poultry Science, 2005)
During the period from July 2002 to June 2003, infectious bursal disease (IBD) was suspected in 101 commercial flocks of broiler chickens on the basis of clinical and post mortem findings in some districts of the Haryana state, India. Bursal samples were collected randomly from 20 flocks for the detection of infectious bursal disease virus (IBDV) by reverse transcription- polymerase chain reaction (RT-PCR) and nested PCR assay. IBDV could be detected in 17 samples as evidenced by amplification of 643 bp fragment of the very variable region of VP2 gene of virus by agarose gel electrophoresis. The authenticity of the amplicons was further confirmed by nested PCR generating amplicons of 552 bp using internal primers. The results of the present study indicated that RT-PCR followed by nested PCR can be used to diagnose field outbreaks of IBD in poultry because of its rapidity, accuracy and sensitivity.